Pengembangan Media Video Animasi Pola Dasar Sistem Meyneke Dalam Mata Kuliah Konstruksi Pola Busana Pada Prodi Pendidikan Kesejahteraan Keluarga Undiksha - Lisanti Zeftiatul Ana; Made Diah Angendari; Putu Agus Mayuni (Universitas Pendidikan Ganesha, 2022)
This research aims to know about: 1) the development of animation video media for the basic pattern of the Meyneke system in the fashion pattern construction course; 2) the feasibility level of the essential Meyneke system animation video media in the fashion pattern construction course based on the assessment of media experts and content experts; 3) student responses in a small group test to the primary animation video media of the Meyneke system in the fashion pattern construction course. The data used in this study are quantitative and qualitative. The subjects of the research are two material experts, two media experts, and six fashion students. The instruments used are interview guidelines and questionnaire sheets. The results are: 1) the development of the meyneke system archetypal animation video media using the PPE model with the planning, production, and evaluation stages, the meyneke system archetypal animation video consists of the intro, opening, material, closing and credits sections packaged in MP4 videos; 2) The feasibility level of animated video media with the basic pattern of the Meyneke system is based on the assessment of content experts, namely 95.215% and media experts with a percentage of 92.105% with the predicate